2020
DOI: 10.1016/j.jsat.2020.108099
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with withdrawal symptoms and anger among people resuscitated from an opioid overdose by take-home naloxone: Exploratory mixed methods analysis

Abstract: during this time, she received funds for travel, training and research materials from GlaxoSmithKline. N.J.K. has also been supported in attending educational meetings by the Lundbeck Institute (2010). J.S. is a researcher and clinician who has advocated for wider preprovision of take-home naloxone, using several types of naloxone. He has also worked with pharmaceutical companies to seek to identify new or improved treatments (including forms of naloxone) from whom, within the last 3 years, his employer (King'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Initial symptoms of anxiety, agitation, and restlessness are distressing to patients, which may lead to increased irritability and aggression. 58 Abstinence in alcohol users after treatment is different, as there is no evidence of urgency of use as is seen with substances such as heroin and crack-cocaine. This can be related to several factors, but those most described in the literature are emotional aspects linked to negative affects that trigger a craving for alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Initial symptoms of anxiety, agitation, and restlessness are distressing to patients, which may lead to increased irritability and aggression. 58 Abstinence in alcohol users after treatment is different, as there is no evidence of urgency of use as is seen with substances such as heroin and crack-cocaine. This can be related to several factors, but those most described in the literature are emotional aspects linked to negative affects that trigger a craving for alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…At the start of the trial, intranasal naloxone was provided in the form of a multi-step atomized nasal naloxone spray assembled by combining a pre-filled luer-lock syringe with a nasal atomizer and spare vial. In August 2017, the trial changed from providing the multistep intranasal naloxone to the single step Narcan ® nasal spray, although participants were still offered the option of receiving the intramuscular device instead (for details see 38 ). Participants were followed up for one year to assess retention of overdose prevention knowledge and to obtain detailed information surrounding overdose events that were witnessed and/or experienced (for detailed information on the RCT see) 29 , 39 …”
Section: Methodsmentioning
confidence: 99%
“…One example is the mooted possibility that the associated sense of safety may paradoxically lead to increased risky behaviour ("risk compensation"): little evidence of this theoretical risk has been found and specific examination of this possibility in a randomized trial found no such evidence [29]. A second example is the concern that excessive naloxone dosing could cause "over-antagonism" [56] with resulting hostility to the person resuscitating the victim alongside further drug-seeking to reverse the reversal: new studies between researchers in London, New York, and Melbourne [57][58][59][60] has explored this phenomenon and their implications for necessary revisions to policy and practice. A third recently identified concern is the reports of low carriage rates of take-home naloxone, a characteristic of possible importance if it leads to missed actions, and which seems to be very variable between settings (<10% in Scotland; >40% in Norway [61,62]), with recent survey comparing different European countries finding considerable variability (forthcoming).…”
Section: Fuller Understandingmentioning
confidence: 99%
“…Naloxone dose needs to be sufficient to reverse the opioid overdose that might cause death. But it is also important to avoid giving excess naloxone which might precipitate acute opioid withdrawal which, in addition to causing unnecessary distress and risk of hostility, might trigger further drug-seeking to reverse the naloxone-trig- gered reversal [56,59,82]. We also need to establish if dose titration can effectively be taught to this new intervention workforce: the principles are simple, as is the practice, requiring the administration of an initial dose, observation of its effect over the next few minutes, then a decision whether a repeat dose is required.…”
Section: Uncertainty About Naloxone Dosementioning
confidence: 99%